The disappearance of the social in American social psychology - Greenwood, John D. (Cambridge University Press, 2004)
The Disappearance of the Social in American Social Psychology is a critical conceptual history of American social psychology. In this challenging work, John Greenwood demarcates the original conception of the social dimensions of cognition, emotion and behaviour and of the discipline of social psychology itself, that was embraced by early twentieth-century American social psychologists. He documents how this fertile conception of social psychological phenomena came to be progressively neglected as the century developed, to the point that scarcely any trace of the original conception of the so.